(untitled) (Bangladesh Journal of Pharmacology, 2012)
This present study explored the anthelmintic activities of crude methanolic extract of dried leaves and stems of Justicia gendarussa, an evergreen plant belonging to the family Acanthaceae. This plant is commonly known as Bishjarul in Bangladesh. Five concentrations (10, 20, 30, 40 and 50 mg/mL) of each extract were studied in the bioassay to determine the paralysis time and death time of the worm, Pheretima posthuma. Methanolic extract of leaves (50 mg/mL) caused paralysis of the worms at 35.33 min and death at 70.67 min while methanolic extract of stem of J. gendarussa caused paralysis at 41.33 min and death at 89.33 min. Albendazole (positive control) paralyzed and killed the worms at 17 min and 48 min, respectively. The study confirms the significant anthelmintic activities of leaves and stems extract of J. gendarussa and therefore demands the isolation of active principles thorough bioassay. This is the first report of anthelmintic activities of J. gendarussa.